Religious worldviews and dialogue: bridging people of different civilizations in shaping a better future - Ali, Muhammad Yousuf; Osmani, Noor Mohammad (2009)
Every religion has its own worldview that provides an outlook for perceiving the reality with a sense of its meaning and values, the central belief system that shapes people’s attitudes, beliefs, and actions; and understanding human-God relationships. In this process, people who adhere to a particular religion tend to explore the phenomena through the lens of religion. However, throughout history it has been observed that religious worldviews have been a strong source of conflict, violence, and destruction (i.e., Crusades of Christian Europe against Muslims). Therefore, dialogue among religions is a vital requirement for establishing world peace and security. This is explicitly significant in the post-9/11 era, when we experience Islamophobia or hatred against Islam (and other religions) based on prejudice and unequivocal ignorance. However, it is proven that efficient and fruitful dialogue among religions has not been accomplished. The aim of this paper is, thus, to delineate the role of religious worldviews in shaping people’s lives, and the significance of inter-religious dialogue in enhancing the bridge among people of different faiths for a prosperous future. It focuses on devising vibrant methodologies and principles for fruitful dialogue among major world religions, and the scope and application of such dialogue in this postmodern civilization. By exploring the common grounds among major religions, this study illustrates that successful inter-religious dialogue is achievable in this globalized era, and Muslims should be the forerunners in this regard. Discussion includes implications of the current findings, and directions for future research. The study generates pragmatic recommendations on devising versatile strategies for prolific dialogue among religions in order to make the world a better place to live in.